Frequency of fatal and non-fatal overdoses and response to grief and loss among people who inject drugs: An unexplored dimension of the opioid overdose crisis. (1st August 2022) - Kenny, Kathleen S.; Kolla, Gillian; Firestone, Michelle; Bannerman, Molly; Greig, Sarah; Flores, B.F.; Dodd, Zoë; Strike, Carol; Bayoumi, Ahmed M.
Abstract: Background: We investigated the relationship between overdose events and grief and loss responses among people who inject drugs. Methods: We conducted a cross-sectional, tablet-based survey with a convenience sample of people who inject drugs (n = 249) from four community-based harm reduction programs in Toronto in 2019. We examined the association between frequency and types of overdose events (own, witnessed, death of significant person) in the last 6 months with grief and loss responses, identified using latent class analysis. Results: Among respondents, 70 (48.6 %) reported 2 or more personal overdoses, 173 (79.5 %) witnessed 2 or more overdoses, and 69 (41.4 %) experienced overdose deaths of 2 or more significant persons in the last 6 months. We identified 2 latent classes with probability of membership of 38.6 % (95 % confidence interval [CI]=31.0, 46.7) for medium/low intensity of responses to grief/loss and 61.4 % (95 % CI= 53.3, 69.0) for severe responses to grief/loss. In adjusted Poisson regression models with robust standard error estimators, severe responses to grief/loss were associated with exposure to two or more own overdoses (prevalence ratio [PR] = 1.44; 95 % CI=1.12, 1.84, p-value=0.004), and having witnessed one (PR=2.09; 95 % CI=1.05, 4.15, p-value=0.04) or witnessed two or more overdoses (PR=2.25; 95 % CI=1.24, 4.09, p-value=0.008). Severe grief/loss responses were also more common in individuals exposed to all three types of overdose events (PR=2.42; 95 % CI=1.08, 5.41, p-value=0.03). Conclusions: Cumulative overdose events were associated with severe responses to grief and loss. Bereavement interventions should consider the complex nature of grief and loss following overdoses. Highlights: This is the first quantitative study of overdose-related grief and loss in people who inject drugs. A higher burden of overdose events was associated with more severe grief and loss responses. Bereavement efforts should consider the complex nature of overdose-related grief and loss.